Analisis Etiologi Kegagalan Perawatan Pulpotomi pada Gigi Desidui: Literature Review - Maulita Misi Nurilyana; Lasmi Dewi Nurnaini (Lembaga Pengembangan Kinerja Dosen, 2026)
Background: Pulpotomy is one of the vital pulp treatments commonly performed on primary teeth with pulp involvement due to deep caries. However, pulpotomy failure remains a significant clinical problem with varying failure rate reported across studies. Aim: This literature review aims to analyze the causes of pulpotomy treatment failure in primary teeth based on current scientific evidence. Method: This study is a qualitative research using a literature review method with secondary data obtained during May 2026 through database searches of PubMed, Science Direct, MDPI, DOAJ, and Garuda using related keywords. The retrieved articles were then selected using a PRISMA flow diagram to obtain several main articles. Results: Based on PRISMA selection, four main articles meeting the inclusion criteria were obtained for this literature review. The review findings indicate that pulpotomy treatment failure in primary teeth is caused by operator clinical technique errors including incomplete coronal pulp tissue removal and inadequate caries excavation resulting in secondary caries formation; inadequate final restoration due to poor marginal adaptation; and inappropriate pulpotomy material selection. Pulpotomy failure may result in pulp necrosis, internal and external root resorption, periapical infection, abscess or fistula, pathological tooth mobility, and gingival inflammation. Conclusion: Pulpotomy failure in primary teeth is influenced by various interrelated factors. Therefore, treatment success depends on the precision of comprehensive procedural execution, necessitating improved clinical standards to minimize the risk of failure.